Postoperative Wound Healing In Oncology Patients, According To Nurses - Žukauskienė, Simona; Čerkauskaitė, Sonata (Slauga. Mokslas ir praktika, 2020)
According to the World Health Organization (WHO), oncological diseases remain among the leading causes of morbidity and mortality worldwide. More than 7 million people die each year from cancer, and more than 12 million new cases of malignant tumors are diagnosed each year [1]. One of the most effective cancer treatment methods is surgical treatment, when the cancer tissue is removed from the human body [2]. The postoperative period begins at the end of the operation and lasts until recovery or adaptation to new conditions. This period lasts and runs very differently, depending on many reasons – the severity and nature of the disease, the complexity and type of surgery, the overall condition of the patient [3].In 2018, an instantaneous quantitative study was conducted in November - December to identify major care problems for postoperative wounds in patients with oncological diseases. The study included 43 nurses from one of the major Kaunas hospitals, who care for patients after oncological operations. According to the nurses, the most frequent complications of postoperative wounds occurring in patients with oncological disease are reddening and swelling of the wound edges, wound swelling, fever and pain, and, to a lesser extent, tension and pulsation, palpable hardening, chills. It has also been found that most nurses believe that the main factors contributing to the complications of these patients’ postoperative wounds – non-compliance with aseptic and antiseptic rules, nosocomial infection and radiation therapy, and factors that have the greatest impact on wound healing, immunity, diabetes, age, anemia.
Keywords: oncology; patients; postoperative nursing; wound care